The Use of Montessori-Based Salt Tray Media in Early Writing Learning for Grade I Students at SDN 46 Banda Aceh - Sinaga, Ria Agustina; Yamin, M.; Mislinawati, Mislinawati (Elementary Education Research, 2023)
Beginning writing learning in grade I looks not very interesting because so far the teacher only uses media in the form of textbooks which are usually readily available, this has caused many students to have not mastered initial writing skills. This is due to the lack of use of media that stimulates students' interest in learning to write the beginning. The formulation of the problem raised in this study is how to use Montessori-based Salt Tray media in learning to write beginning in grade I students at SDN 46 Banda Aceh. This study aims to describe the use of Montessori-based Salt Tray media in learning to write beginning in grade I students of SDN 46 Banda Aceh. This study uses a descriptive qualitative research method. The subjects in this study were class I teachers as homeroom teachers at the school. The data collection techniques through observation and interviews. The data collected in this study were teacher and student observation sheets and interviews with a total of 11 questions. Then the data were analyzed with 3 stages, namely data reduction, data presentation, and drawing conclusions. The results showed that the implementation of learning to write beginning using Montessori-based Salt Tray media for class I students at SDN 46 Banda Aceh went very well, and had integrated it with Montessori principles. The existence of Montessori-based Salt Tray media has helped teachers convey material, and students are also enthusiastic about learning while playing, and are more focused on the material being taught.